A functional barley-based fermented soup (tarhana) with high β-glucan content - Koksel, Hamit; Ozkan, Kubra; Tekin-Cakmak, Zeynep Hazal; Karasu, Salih; Kahraman, Kevser; Oruc, Sena; Sagdic, Osman; Sestili, Francesco (SPRINGER, 2025)
This study investigates the impact of using different flours, including high beta-glucan barley, on the nutritional properties of tarhana. Mineral composition, phenolic content, and antioxidant capacity of tarhana powder samples produced using flours of high beta-glucan hull-less barley (cv. Chifaa; ChF), hull-less barley cv. Yalin (YF), bread wheat cv. Tosunbey (white flour: TWF1 and whole wheat flour: TWF2). Furthermore, in vitro glycemic index (GI), pasting properties, and RVA soup index of their soups were investigated. Tarhana made with Chifaa barley flour (Tar-ChF) exhibited significantly higher levels of key minerals (K, Mg, Ca), beta-glucan and total phenolic content compared to those made with other flours (Tar YF, Tar TWF1, and Tar TWF2). Barley tarhana samples also showed greater antioxidant activity of bound phenolic fractions and lower GI values, indicating a healthier profile. The study highlights the potential of high beta-glucan barley flour to enhance tarhana's nutritional benefits without significantly affecting its sensory properties, such as color and viscosity. This research supports the integration of health-promoting ingredients like barley flour into traditional Mediterranean foods to improve their nutritional quality.
Keywords: Tarhana; beta-glucan; Hull-less barley; Glycemic index; RVA soup index; ANTIOXIDANT ACTIVITY; PHENOLIC CONTENT; FOOD-PRODUCTS; CEREAL FOOD; HYDROLYSIS; FRACTIONS; RESPONSES; INSULIN; GLUCOSE; FIBERS; Food Science & Technology